Pengaruh CAR, LDR dan NIM terhadap ROA Pada Bank Umum yang Terdaftar di BEI - Listy Septia Cahyani; Fifi Afiyanti Tripuspitorini; Ade Ali Nurdin (Indonesian Journal of Economics and Management, 2022)
This purpose of the final study is to analyze the effect of CAR, LDR and NIM on ROA in Commercial Banks Listed on the Indonesia Stock Exchange (IDX) for the period 2015 -2019. In this study, using the type of secondary data from 22 samples of commercial banks listed on the Indonesia Stock Exchange (IDX). This research method used is a quantitative method. The results showed that simultaneously Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) had an effect on Return On Assets (ROA). Partially shows that the Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) have a significant effect on Return On Assets (ROA). Meanwhile, Loan to Deposit Ratio (LDR) has no significant effect on Return On Assets (ROA).